Homeless Health Care Simulated Patient Case - Susan Glick; David Buchanan; Louis Rohr; Laura Kehoe (Association of American Medical Colleges, 2007)
Abstract Introduction In order to appropriately care for a patient who is homeless, physicians must recognize the significance of homelessness to health and respond to the unique challenges that homelessness presents. Unfortunately, medical students and physicians rarely receive formal training in homeless health care. This simulated patient (SP) case aims to teach learners about the presentation, diagnosis, and management of homelessness and to evaluate their skill in recognizing, screening for, and responding to patients who are homeless. Methods The program was held in a SP laboratory. Learners attended the program in groups of four. Learners were first oriented to the program before independently evaluating the SP and documenting the history, physical examination, assessment, and plan in a written clinic note. After the evaluation a faculty preceptor led a postclinic conference. Results Twelve primary care internal medicine residents participated in this case. Of these, seven found the case highly educational and five found it very educational; seven found the case highly realistic and five found it very realistic. Eleven of the residents recommended that the residency program offer another SP program in the future. Of the twelve residents, four had participated in a required rotation in homeless health care, and eight had received no formal training in homeless health care but had extensive experience caring for homeless patients in a large, urban public hospital/clinic. Of the four residents with extensive instruction, three (75%) recognized the relationship between homelessness and diabetes control and asked about this explicitly. These three residents (75%) gave the patient suggestions about how and where to store his insulin. Three of the residents (75%) referred the patient to the social worker. Of the eight residents without formal training, only four (50%) recognized the relationship between homelessness and diabetes control and asked about this explicitly. None of the residents provided the patient with suggestions about how and where to store his insulin. Seven of the residents (88%) referred the patient to the social worker. Discussion Primary care internal medicine residents without formal training in homeless health care are less likely to appreciate the relationship between homelessness and control of chronic illness, and are less likely to incorporate homelessness into their management plans. Both groups of residents (those with and those without formal training in homeless health care) recognize the need to refer patients who are homeless to a social worker. The apparent belief that responding to homelessness is the responsibility of the social worker and not necessarily the physician may result in a missed opportunity to improve the care of chronic disease for patients who are homeless.